Intention to use telemedicine based on the Unified Theory of Acceptance and Use of Technology Model - Indrayathi, Ayu; Julyari, Dewa Ayu Vera; Pradnyani, Putu Erma; Luh Putu Sinthya Ulandari; Soukaina Hilal (Public Health and Preventive Medicine Archive, 2023)
Background and purpose: Due to COVID-19 pandemic, demand for technology in daily interaction has rapidly grown to ease communication while maintaining physical distance. This study examines the determinants of the intention to use telemedicine using the Unified Theory of Acceptance and Use of Technology (UTAUT) Model. Methods: This cross-sectional study was an online survey using Google Form application conducted from March 11 to May 3, 2021. The inclusion criteria of samples were aged 18 years or older, residing in Bali during the data collection period and knowing telemedicine health services. Variables collected include intention to use telemedicine, demographic characteristics of respondents and UTAUT variables, namely performance expectancy, business expectancy, social influences, and facilitation conditions. The statistical test used is simple and multiple logistic regression analysis. Results: Of 458 survey respondents, 287 were included for analysis due to incomplete data.  Almost half of the respondents (48.8%) was aged <25 years old, the majority were female (80.51%) and around two-thirds, were studying in university, being employed and earning income. We found most respondents (57.14%) were highly interested in telemedicine services. The logistic regression analysis showed that performance expectations, business expectations, social influence, and facilitating conditions were significantly associated with people's interest in telemedicine in Bali. Conclusion: Telemedicine is relatively popular in Bali, Indonesia.  Performance expectancy, effort expectancy, and social influence are the predominant factors influencing the intention to use telemedicine. It shows the potential to employ telemedicine service to cover the inadequate distribution of health professionals and healthcare in Indonesia.